Neuronal input triggers Ca2+ influx through AMPA receptors and voltage‐gated Ca2+ channels in oligodendrocytes. Issue 10 (17th July 2019) - Barron, Tara; Kim, Jun Hee
Abstract: Communication between neurons and developing oligodendrocytes (OLs) leading to OL Ca 2+ rise is critical for axon myelination and OL development. Here, we investigate signaling factors and sources of Ca 2+ rise in OLs in the mouse brainstem. Glutamate puff or axon fiber stimulation induces a Ca 2+ rise in pre‐myelinating OLs, which is primarily mediated by Ca 2+ ‐permeable AMPA receptors. During glutamate application, inward currents via AMPA receptors and elevated extracellular K + caused by increased neuronal activity collectively lead to OL depolarization, triggering Ca 2+ influx via P/Q‐ and L‐type voltage‐gated Ca 2+ (Cav ) channels. Thus, glutamate is a key signaling factor in dynamic communication between neurons and OLs that triggers Ca 2+ transients via AMPARs and Cav channels in developing OLs. The results provide a mechanism for OL Ca 2+ dynamics in response to neuronal input, which has implications for OL development and myelination. Main points: Glutamate signaling from neurons via oligodendrocyte AMPA receptors leads to Ca 2+ rise in oligodendrocytes. Neuronal activity sufficiently depolarizes oligodendrocytes to result in Ca 2+ influx through L‐ and P/Q‐type voltage‐gated Ca 2+ channels.